The mental health lead. (2nd May 2021) - Preston, Sam
Abstract : The government wants every school to have a designated mental health lead in place by 2025 and has begun to fund training to support this goal. In light of the pandemic's impact, the role could well be a crucial part of recovery. Sam Preston looks at what it will entail